COMPARATIVE STUDY ON CLINICAL EFFICACY AND SAFETY OF FORMULATED AND MARKETED MYRRH EXTRACT IN CAPSULES - MOHAMED DAWOUD,; ABDOU, RANDA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The development of myrrh extract from natural origin capable of eradicating schistosomal infection has gained the interest of many scientists. Recently, myrrh extract is considered as the drug of choice from natural origin used to treat schistosomiasis. This study was performed to evaluate the safety and efficacy of hard gelatin capsules of myrrh extract in the treatment of Schistosoma mansoni compared to Mirazid which is the only herbal drug present in the market. Methods: In the present study, the clinical evaluation of different doses of formulated myrrh extract hard gelatin capsules against different grades of S. mansoni infections (mild, moderate, and heavy) was carried out and compared with marketed soft gelatin capsules Mirazid. Results: In all types of S. mansoni infection, it was clear that the efficacy of n-hexane and alcohol myrrh extracts hard gelatin capsules was higher than or equal to that of Mirazid soft gelatin capsules. Conclusion: Hard gelatin capsules of myrrh extract (mixed doses) are more effective and more economic as a pharmaceutical dosage form for pharmaceutical manufacturers than Mirazid soft gelatin capsules. Consequently, with its lower price, it can reach the poor patient which is the main patient of schistosomiasis.